Ethnicity and Religion in the Identity Politics: A Historical Reflection of Jakarta Regional Head Election in 2017 - Afif, Yusmicha Ulya; Suryaningtyas, Afrin; Maisaroh, Phuji (Sultan Journal of Social Sciences and Humanities, 2024)
DKI Jakarta is a reflection of the diversity of races, nations and religions of Indonesia in the form of a city. From this diversity, DKI Jakarta has always been in the spotlight of other regions, especially politics. The governance system that is run by DKI Jakarta has always been the focus of attention, 2017 has become a political year for the election of the governor of DKI Jakarta with fierce betting both candidates for incumbent or challenger. The candidates are Batsuki Tjahatja Purnama (Ahok) - Djarot, Anies Baswedan-Sandiaga Uno, and partner Agus Harimurti Yudhoyono-Sylviana. In the first round, the pair Agus-Sylvi had to be eliminated while the pair Ahok-Djarot and Anies-Sandiaga successfully walked into the second round. Religious and ethnic elements contributed to the final results of the elections. Prospective leaders who represent the majority of the population of the region to be led, have better capital than prospective leaders who represent a minority in a country. In terms of religion, Anies-Sandiaga has similarities with the majority of the population of DKI Jakarta, which 85% of the population is Muslim. While Batsuki Tjahatja Purnama came from two layers of minority groups in Indonesia, namely Chinese and Christians. In terms of winning strategy, Anies-Sandiaga is racing to prioritize aspects of primordialism. Whereas Ahok-Djarot did not make ethnicity or religion the main issue but diversity was prioritized. Although the use of identity politics is not prohibited, the excessive use of the identity of the candidate can gradually damage the Indonesian diversity. In this scientific article, the researcher seeks to elaborate on the misuse of ethnicity and religion for political interests in the DKI Jakarta Regional Head Election in 2017. The use of ethnic and religious identities in each political year is interesting to be examined, because both of these issues have an impact quite meaningful in achieving political interests and overthrowing the opposing party.